Implementing Analytical Procedures in Predicting Return on Assets Through the Mediating Role of Regression Analysis: An Applied Study in Mosul Bank for Development and Investment - Abbas, Fadhil Hussein (University of Thi-Qar Journal, 2025)
The present study highlights the influence of using analytical procedures through the application of regression analysis as an analytical procedure in predicting the rate of return on banking assets. This approach is applied to the financial statements of Mosul Bank for Development and Investment to obtain reasonable assurance as to whether the rate of return on assets, based on the data contained in the financial statements, will continue in the near future. The results of the analysis demonstrate that the expected rate of return on assets for 2024 is (1.21%), compared to the years of the study sample. This indicates that Mosul Bank for Development and Investment does not possess a good rate of return on assets, enabling it to confront emergency and unexpected situations resulting from future economic changes and events. Furthermore, the phenomenon of financial failure is one of the most important phenomena requiring careful consideration and investigation into its causes, as its consequences are now reflected on both internal and external stakeholders. To obtain this objective, the regression model was applied to Mosul Bank for Development and Investment, a sample of Iraqi banks listed on the Iraq Stock Exchange, to determine the bank’s ability to confront any risks or difficulties that may arise as a result of fluctuations in the Iraqi economy. The study recommends enhancing the use of quantitative analytical procedures in accounting and auditing practices, with a focus on developing the skills of analysts and auditors in utilizing analytical statistical tools, such as regression analysis, to provide more accurate and objective assessments of financial performance. It also emphasizes the importance of integrating these methods into accounting and control systems to improve the effectiveness of financial forecasting and strengthen the response to potential risks.